Penentuan Kandungan Phthalate Plastisizer Dehp (Bis (2-Ethylhexyl) Phthalate) pada Botol Minuman Plastik dengan Metode EN71-5 Menggunakan GC-MS - Budhi Indrawijaya; Wisnu Setya Nugraha (Jurnal Ilmiah Teknik Kimia, 2021)
Plastic-based products have become daily human needs. From so many plastic products on the market, drinking bottles are one of them. Behind the color, shape and size variations that we find on the market, one thing we must know, the type of plastic base material used in making these drinking bottles and its product safety. One of the risk is the use of plasticizers as additives which work to increase the flexibility and durability of the plastic materials. These plasticizers can contain dangerous substances namely DEHP (Bis (2-ethylhexyl) phthalate), which is a type of ester phthalates. Studies conducted have found that phthalates can affect the development of the male reproductive system, or can reduce the level of the male testosterone hormone. Phthalates can cause cancer. Analysis of the levels of phthalates compounds in plastic materials can be done by the EN71-5 method. Sample preparation was carried out by extraction using a soxhlet extractor and n-Hexane organic solvent, then the samples were analyzed by GC-MS instrument. From the analysis results obtained the content of DEHP phthalates (Bis (2-ethylhexyl) phthalates) is below the Instrument detection limit or it can be concluded that the compound is not detected in the sample, so it meets the threshold for goods containing hazardous chemicals according to Regulation of the Minister of Trade No. 18 of 2019